Evaluation of 1,5-Anhydroglucitol as a Biomarker for Type 2 Diabetes Mellitus in Patients without Overt Nephropathy (Brazilian Journal of Pharmaceutical Sciences, 2022)
1,5-Anhydroglucitol (1,5-AG) is a non-fasting glycemic marker that responds to hyperglycemia excursions. The reduction in serum levels of 1,5-AG is associated with an increase in postprandial glycemia and glycosuria, phenomena that increase the risk and severity of diabetic complications. The objective is to assess the ability of 1,5-AG to discriminate type 2 diabetes (T2D) patients without overt kidney disease, for screening or diagnostic purposes. The Human Research Ethics Committee of Universidade Federal do Paraná (UFPR) approved the project. Serum samples from 567 individuals classified as healthy subjects (n = 291) and T2D (n = 276) with moderate glycemic control (HbA1c of 7-8%), matched by gender, were analyzed. Serum 1,5-AG levels were measured using an automated enzymatic method (GlycoMark, Inc.). Receiver Operating Characteristic (ROC) curve analysis for 1,5- AG showed sensibility of 65.3% and specificity of 91.1% to detect T2D at cut-off point of 92 µmol/L. The results were similar to the groups’ discrimination by glycemia (sensibility/specificity, 62.2%; 89.0%) at cut-off point of 6.3 mmol/L. HbA1c was the best discriminator (sensibility/specificity, 87.4%; 94.2%) at a cut-off point of 5.8% (40 mmol/mol). The serum 1,5-AG concentration was not able to discriminate T2D in the presence of moderate glycemic control with no overt nephropathy.